Identifying opportunities to optimize mass drug administration for soil-transmitted helminths: A visualization and descriptive analysis using process mapping - IBIKOUNLE, MOUDACHIROU (My University, 2024)
Background Thecontrol of soil-transmitted helminths (STH) is achieved through mass drug administration (MDA) with deworming medications targeting children and other high-risk groups. Recent evidence suggests that it may be possible to interrupt STH transmission by deworm ing individuals of all ages via community-wide MDA (cMDA). However, a change in delivery platforms will require altering implementation processes. Methods We used process mapping, an operational research methodology, to describe the activities required for effective implementation of school-based and cMDA in 18 heterogenous areas andover three years in Benin, India, and Malawi. Planned activities were identified during workshops prior to initiation of a large cMDA trial (the DeWorm3 trial). The process maps were updated annually post-implementation, including adding or removing activities (e.g., adaptations) and determining whether activities occurred according to plan. Descriptive analyses were performed to quantify differences and similarities at baseline and over three implementation years. Comparative analyses were also conducted between study sites and areas implementing school-based vs. cMDA. Digitized process maps were developed to provide a visualization of MDA processes and inspected to identify implementation bottlenecks and inefficient activity flows.
Keywords: mass drug administration; soil-transmitted; helminths; descriptive analysis; process mapping